Pengaruh Dimensi Geometris Cerobong Pemanasan Awal Terhadap Atomisasi Bahan Bakar Biodiesel Dengan Atomizer Berbasis Air-Assist - Aqillah, Zelfa Graha; Ghurri, Ainul; Parwata, I Made (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract The use of cooking oil produces wastes that we can then reused, that is used as fuels. Oils and biofuels have high viscosity characteristics, and a burner design is very important toward an ideal result. Utilization of an airassisted atomizer with far ad-vantages for spraying fuel, added with heating funnel, could overcome the high viscos-ity of the fuels to produce finer spray with better atomization result. This research focus on analyzing the effect of heating funnel dimensions on fuel atomization with air-assist based atomizer. This study used of fuel biodiesel. The research showed that an air-assisted atomizer spray with heating funnel is highly efficient for high viscosity fuels. The atomization result is better as the length dimension of the heating funnel increased. This is because longer funnel dimen-sion result in a greater heat absolved by the atomized fuel. It was also proven in the study where the long dimension of the heating funnel which has a larger size, a length of 14 cm, has better results than 12 cm and 10 cm long heating funnel, with atomization on biodiesel fuel of 90.9% Keywords: Atomization, Spray, Air-Assist Atomizer, Nozzle, preheating, Heating funnel